2019
DOI: 10.3390/ijerph16244945
|View full text |Cite
|
Sign up to set email alerts
|

Culture, Work, and Subjective Well-Being: The Role of LMX and Resilience in Spanish and Chinese Cultures

Abstract: Globalization and interdependencies among nations require a better understanding of the influence of culture on organizational processes. In order to succeed in global business, leaders have to respond to practices that may be different in diverse cultures. This study was conducted within the framework of the leader member exchange approach and from a positive perspective of organizations linking successful businesses and workers’ well-being. The aim of this study was to examine whether the quality of the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 77 publications
(93 reference statements)
0
11
0
Order By: Relevance
“…LMX is also found to be a positive predictor of life satisfaction among Chinese and Spanish workers, and this relationship is moderated by resilience (González-Navarro et al, 2019).…”
Section: Leader-member Exchange (Lmx) and Subjective Well-beingmentioning
confidence: 87%
“…LMX is also found to be a positive predictor of life satisfaction among Chinese and Spanish workers, and this relationship is moderated by resilience (González-Navarro et al, 2019).…”
Section: Leader-member Exchange (Lmx) and Subjective Well-beingmentioning
confidence: 87%
“…In meta-analytic research, Martin et al (2016) have shown that a high-quality LMX relationship is essential for the attitudes and performance of employees. For instance, LMX has been found to be related to employees’ proactive behavior ( Lai et al, 2019 ), engagement and job satisfaction ( Volmer et al, 2011 ; González-Navarro et al, 2019 ), as well as their resilience ( Kakkar, 2019 ). Moreover, González-Navarro et al (2019) found a positive association between LMX and job engagement.…”
Section: An Applied Examplementioning
confidence: 99%
“…For instance, LMX has been found to be related to employees’ proactive behavior ( Lai et al, 2019 ), engagement and job satisfaction ( Volmer et al, 2011 ; González-Navarro et al, 2019 ), as well as their resilience ( Kakkar, 2019 ). Moreover, González-Navarro et al (2019) found a positive association between LMX and job engagement. Research has also shown that PsyCap can be significantly enhanced through proximity, trust, and support that leaders can provide their employees with ( Law et al, 2010 ; Kakkar, 2019 ) and that LMX-quality can predict PsyCap profiles ( Luthans et al, 2004 ).…”
Section: An Applied Examplementioning
confidence: 99%
“…Empirical studies have consistently evidenced a positive relationship between work engagement and employee well-being, including its relevant domains (e.g., life satisfaction) in different cultural contexts (e.g., [ 42 , 43 , 44 , 45 , 46 ]). In a two-year longitudinal study involving 1196 employees from an industrial machinery company in Japan, Shimazu and colleagues found that the three subdomains of work engagement (i.e., vigor, dedication, and absorption) are positively correlated with improvement in psychological well-being, as indexed by job satisfaction and family satisfaction ( r = 0.09–0.16) [ 47 ].…”
Section: Introductionmentioning
confidence: 99%